Morphology and Histology Identification of Fungal Endophytes from Oil Palm Roots in Ganoderma boninense Endemic Area - ELIZABETH CAROLINE SITUMORANG; ANDRIESSA PRAMESWARA; HANA CHRISTINE SINTHYA; NURITA TORUAN-MATHIUS; TONY LIWANG (Microbiology Indonesia, 2013)
Endophytic fungi defined as fungi that colonize internal plant tissues without causing visible damage to their host plant. As they are internal colonisers, therefore more able to compete within the vascular systems with capacity to arrest the spread of pathogens such as Ganoderma boninense causal agent of Basal Stem Rot (BSR) disease in oil palm. Endophytic microbes acted against plant pathogen by antibiosis mechanism, nutrient and space competition, and induce plant pathogen resistance by producing metabolites. The objective of the present study was to identify endophytic fungi from oil palm roots in G. boninense endemic area Padang Halaban Estate, North Sumatera, based on morphological and histological character. At each site, five random palms were sampled. Seventy five endophytic fungi had been isolated and selected from BSR symptomless palm root. Identification of fungal endophytes were carried out by observing the reproductive structures (sexual and asexual) under a light-field microscope with camera attachment. Seventy five isolates were classified to eight genera, consisting of Trichoderma (20), Fusarium (10), Aspergillus (5), Penicillium (5), Gliocladium (4), Phoma (4), Alternaria (4), and Curvularia (3). Twenty others were unidentified due to sterile mycelia.